Development and evaluation of web service-based interactive and simulated learning environment for computer numerical control - Wu, Wen-Hsiung; Chen, Wei-Fan; Fang, Lung-Ching; Lu, Chao-Wei (Computer applications in engineering education, 2010)
Multimedia technology and Internet applications are important tools for teaching and learning in engineering education. Nowadays online simulative environments are indispensable tools for teaching computer numerical control (CNC) course in mechanical engineering. Nevertheless, past studies seldom designed CNC code or program error handling mechanisms, and failed to use new emergent technologies and applications. This study proposed a design for a WSISLE‐CNC (web service‐based interactive and simulated learning environment for CNC) based on Web service technology. A questionnaire survey from vocational school instructors and students revealed a high degree of enthusiasm for this proposed approach. In summary, the main contributions of this study to engineering education are: (1) development of several types of CNC code or program error handling mechanisms and applications, and (2) use of Web service concepts and technology to develop various kinds of CNC simulation services. © 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 18: 407–422, 2010; View this article online at wileyonlinelibrary.com; DOI 10.1002/cae.20147